Asymptomatic giant coronary aneurysm in an adolescent with Behcet's syndrome - Kahn Philip J; Yazici Yusuf; Argilla Michael; Srichai Monvadi; Levy Deborah M (BMC, 2012)
Abstract Objective Behcet's is an idiopathic multi-organ syndrome, which may have onset during childhood. Vascular involvement is uncommon, with rarely reported coronary aneurysm formation. We present a case report of a teenager girl who developed recalcitrant life-threatening Behcet's vasculitis, involving both small and large venous and arterial systems including a giant coronary aneurysm. Case report De-identified data were collected retrospectively in case report format. Although our sixteen year old female with Behcet's vasculitis had resolution of many arterial aneurysms, she had persistent venous thrombosis of large vessels, as well as persistent, giant arterial aneurysms requiring intra-arterial coiling of a lumbar artery and coronary bypass grafting despite intensive immunosuppression including glucocorticoids, cyclophosphamide, infliximab, methotrexate, azathioprine and intravenous immunoglobulin. Conclusions Vascular manifestations may be seen in Behcet's syndrome, including asymptomatic coronary aneurysm, which may be refractory to immunosuppression and ultimately require surgical intervention. Increased awareness is essential for prompt diagnosis and management.